Seed Priming and Coating by Nano-Scale Zinc Oxide Particles Improved Vegetative Growth, Yield and Quality of Fodder Maize (Zea mays) - Tondey, Manisha; Kalia, Anu; Singh, Alla; Dheri, Gurmeet Singh; Taggar, Monica Sachdeva; Nepovimova, Eugenie; Krejcar, Ondrej; Kuca, Kamil (Agronomy (Basel), 2021)
Nano-fertilizers of essential plant nutrients, including micronutrients, have the potential to improve nutrient use efficiency and productivity of field crops in deficient soils. The present study reports the comparative influence of zinc oxide nanoparticles (ZnONPs) and bulk Zn salt (ZnSO4) on the growth, yield, and quality of fodder maize (Zea mays) (var. J-1006) cultivated under field conditions in the year 2019. Three levels (0, 20, and 40 mg L−1) of Zn fertilizers were used for seed priming and coating in triplicate following the randomized complete block design model. An increase in vegetative and yield parameters (number of plants, plant height, stover yield, plant biomass), acid detergent fiber (ADF%), and hemicellulose contents and shoot zinc (Zn) content on treatment of seeds with ZnONPs (20 mg L−1) concentration as compared to bulk ZnSO4 and control treatments was observed. The application of ZnONPs (40 mg L−1) significantly enhanced the total chlorophyll content, available soil nitrogen and phosphorus, neutral detergent fiber (NDF%), and cellulose contents and improved the total soil microbial counts and soil enzyme activities (dehydrogenase, acid and alkaline phosphatase enzyme activities), whereas a significant increase in available soil potassium and zinc contents was recorded under ZnONPs (20 mg L−1) treatments. These findings suggest an encouraging effect on the growth and yield attributing characteristics of fodder maize after ZnONPs seed coating at low concentration. Furthermore, ZnONPs seed coating can also be considered an effective tool for the delivery of Zn micronutrient to fodder maize crop.